Papers of Lowitja O'Donoghue - O'Donoghue, Lowitja, 1932-2024 (1940)
This collection comprises papers spanning the early years and working career of Lowitja O’Donoghue, advocate for Indigenous people. Much of the collection relates to Lowitja’s senior roles as chair of Aboriginal Hostels, chair of Aboriginal Development Commission and the Aboriginal and Torres Strait Islander Commission (ATSIC). There are reports, papers and correspondence relating to Lowitja’s extensive and varied involvement in associations and movements for Indigenous health welfare and human rights. There are also biographical papers, photographs, published books and articles, notebooks and diary schedules, loose transcripts and a boxed 3 volume collection of speeches. Also included are commemorative and personal objects from Lowijta O’Donoghue such as torches and tracksuits from the Olympics and ParaOlympics, her wedding dress and decorations as well as plaques of appreciation, honours and awards.
Manuscript reference number: MS 10445.
Cultural Sensitivity Advisory Notice: Aboriginal, Torres Strait Islander and other First Nations people are advised that this collection may contain names, recordings and images of deceased people and other content that may be culturally sensitive. Please also be aware that you may see certain words or descriptions within these works which reflect the author’s attitude, or that of the period in which the works were created, and may now be considered inaccurate, inappropriate or offensive.
Aboriginal rights activist, nurse and senior public servant. Lowitja O'Donoghue was the Founding Chair of the Aboriginal and Torres Strait Islander Commission, 1990-1996. Further biographical information available online at
Keywords: O'Donoghue, Lowitja, -- 1932-2024 -- Archives; Aboriginal Hostels Limited; Australia. -- Aboriginal Development Commission; Australia. -- Aboriginal and Torres Strait Islander Commission; Women, Aboriginal Australian -- Archives; Nurses -- Australia -- Archives; Human rights workers -- Australia -- Archives; Political activists, Aboriginal Australian -- Australia -- Archives; Public officers -- Australia -- Archives; Aboriginal rights activists; Public servants